CONTENT OF MODERN EDUCATION: CHOICE OF THE PATH - V. A. Testov (Образование и наука)
Introduction. Modernization of education and formation of its content according to modern realities and the prospects of society development appear to be the most acute issues since the future of the country depends on their decision. The aim of the article is to justify the need to rely on the achievements of pedagogical science, the use of profound and fruitful scientific ideas of outstanding Russian scientists and pedagogues, and the participation of the pedagogical community when carrying out educational reforms. Methodology and research methods. The following theoretical methods were used: analysis of pedagogical and methodical literature, normative documents; historical, comparative, and logical analyses of the content of education; the forecasting. Resultsand scientific novelty. The article identifies two main areas in the choice of strategic goals of education. The future of Russia depends on the chosen direction. The first is the disclosure of the abilities of each student, the development of analytical abilities and critical thinking, the education of a person ready for life in a high-tech, competitive world. The second is to nurture a qualified consumer who can skillfully use the results of the creativity of others and ready for life in the so-called «skilled society». The first direction requires the presence of a fundamental education oriented to strategic perspectives; the second – utilitarian-practical education, oriented to today’s requests. The close interrelation of knowledge and skills is demonstrated on the basis of the concept of education content; wherein the key aspect is the idea of sociocultural experience broadcasting for the new generations. It is stated that a person without knowledge turns into a robot unable to act independently in critical situations. The feasibility of a reasonable combination of conservatism and innovation under the change of the education content and reforms implementation is approved. This highly sensitive and complex educational system requires «careful handling». The most effective management system is possible only through less interference into its internal processes; the imposition of fixed plans and schemes may carry the system destruction, as pointed out in the synergetic methodology thesis. Practical significance. The materials of the present research contribute to forecasting of possible scenarios of education development. The study results may be of interest both for methodologists and specialists of education management, teachers and lecturers of higher schools, i.e. all those who are interested in the prosperous future for the Russian education system, and for the country in general.